Software contable y su incidencia en el Departamento de Finanzas del Gobierno Autónomo Descentralizado San Jacinto de Yaguachi - Orellana Risco, Melannie Anahi (2021)
This study was carried out in order to allow us to recognize and apply accounting software which will help our company, these programs will facilitate the use of them in our operations to record, classify, process information on all our accounting transactions to make effective the execution in the finance department of the Decentralized Autonomous Government of San Jacinto de Yaguachi. For the development of this work, a previous observation, investigation was carried out. Survey of the directive and administrative personnel by obtaining said information, an analysis of it was carried out in order to then obtain correct solutions according to the need through this accounting software its correct use, function and development which should be applied according to the need business as there are several types of accounting programs depending on the company. Thus we will have that the accounting software was directed to a financial department since it has a typology according to its need. Through the study of this case, the application of accounting software that contributes to the management of the information of the accounting operations and its correct systematization could be evidenced because it constitutes a fundamental tool to maintain order in the accounts of a company , when being executed in the presentation of financial statements, helping to have an adequate control and thus errors can be anticipated or problems related to accounting in the financial department can be avoided.